1979
DOI: 10.1021/bk-1979-0099.ch001
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Organophosphorus Insecticides in Aquatic Organisms, with Special Emphasis on Fenitrothion

Abstract: The organophosphorus compounds constitute one major group of insecticides, and a certain portion thereof may be transported to the aquatic environment resulting either from the actual use on paddy fields or from unavoidable transmittance to waterways. However, possibly because of its relatively shorter persistence, the translocation and transformation of organophosphorus compounds in the aquatic environment has not been extensively investigated as compared with more persistent organοchlorine compounds.Fenitrot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 4 publications
2
15
0
Order By: Relevance
“…Fish CYP1A activity has been found to be involved in organophosphate pesticides metabolism (Flammarion et al 1998;Kitamura et al 2000;Schlenk 2005) including in fenitrothion metabolism (Miyamoto et al 1979). In the present study, EROD activity was found to be significantly increased in seabass juveniles exposed to fenitrothion at concentrations equal or higher than 1 mg l -1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Fish CYP1A activity has been found to be involved in organophosphate pesticides metabolism (Flammarion et al 1998;Kitamura et al 2000;Schlenk 2005) including in fenitrothion metabolism (Miyamoto et al 1979). In the present study, EROD activity was found to be significantly increased in seabass juveniles exposed to fenitrothion at concentrations equal or higher than 1 mg l -1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although closed systems equipped with volatile traps have been used to improve the recovery of 14 C, there was a failure to demonstrate the advantage of the modified system either because of insufficient volatile trapping or because of inadequate bottom sediment analyses Tsuge et al 1976). Most model ecosystem studies have utilized single applications, although Miyamoto et al (1979) examined the effect of multiple applications of fenitrothion (41) in a recirculating system; these authors reported no increase in bioaccumulation as compared with a single application. Although model systems may allow collection of valuable information on the interactions among several species, linked by a food web, obtaining time-dependent distribution data for tested pesticides and their metabolites is difficult.…”
Section: Model Ecosystemsmentioning
confidence: 99%
“…Miyamoto et al (1966) studied the degradation of fenitrothion by B. subtilis. The major metabolite was aminofenitrothion, and other minor metabolites detected were dimethyl thiophosphoric acid and desmethyl fenitrothion.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Pathway of degradation of fenitrothion by B. subtilis in environment. This figure was adopted from Miyamoto et al (1966) with slight modifications. Aminofenitrothion was the major metabolite of fenitrothion in B. subtilis.…”
Section: Wwwintechopencommentioning
confidence: 99%